Characteristics of In-Hospital Mortality among Patients with Acute Coronary Syndrome: A Single-Center Study in West Java, Indonesia - Dennis Bonang Tessy (Universitas Padjadjaran, 2021)
Background: Acute Coronary Syndrome (ACS) is a severe manifestation of coronary artery disease, classified into unstable angina (UA), non-ST-segment elevation myocardial infarction (NSTEMI), and ST-segment elevation myocardial infarction (STEMI). In-hospital mortality in patients with ACS remains high despite the advancement of therapy. This study aimed to evaluate the characteristics of in-hospital mortality among ACS patients in West Java, Indonesia.